The hydrothermal system associated with Miocene Chimpa volcano, Central Andes. Implications on potential mineralization. (January 2021) - Bustos, Emilce; Simón, Valeria; Arnosio, Marcelo; Norini, Gianluca; Ducart, Diego Fernando; Suzaño, Néstor
Abstract: Miocene volcanism in the central sector of the Puna plateau, in the back–arc region of the Central Andes, has important economic potential, because it is associated with many epithermal ore deposits. Chimpa volcano is one of the largest stratovolcanoes of this region, hosting hydrothermal alteration. In order to map and characterize the hydrothermal alteration, multispectral ASTER satellite imagery, fieldwork, petrography, XRD and Raman spectroscopy have been used. Our study allowed identifying two alteration zones: alunite + illite + jarosite, and alunite + illite. The alunite + illite + jarosite zone occurs mainly in the center of Chimpa volcano, corresponding to the vent area and covering an area of ~0.02 km 2 . The alunite + illite zone covers a wider area mainly surrounding the alunite + illite + jarosite region, extending to the east and west and covering an area of ~2.5 km 2 . Small altered zones observed away from the vent area have been incorporated in mass-wasting and sector collapse deposits. Therefore, the hydrothermal alteration zone may be actually narrower than the area occupied by altered rocks. The absence of ore minerals indicates a potential barren hydrothermal system. However, the recognized alteration zones, together with the presence of vuggy silica and hypogene alunite, suggest that Chimpa volcano could host a volcanic-hydrothermal leached system related to the emplacement of a volcanic dome complex in the summit area. The hydrothermal system was set up in the final stage or immediately after the dome emplacement phase. Further prospection studies, such as geophysical techniques and drilling, should be focused on finding out if the Chimpa volcano hosts a mineralized system or is a non-economic acidic alteration. Highlights: Alunite + illite + jarosite, and alunite + illite alteration zones were detected. Altered material move away from the vent because the collapse. Chimpa volcano could host a volcanic-hydrothermal leached system. Prospection is necessary to define if the system is mineralized or barren.